Non-invasive in vivo monitoring of transplanted stem cells in 3D-bioprinted constructs using near-infrared fluorescent imaging - Kim, Soon Hee; Kwon, Jin Seon; Cho, Jae Gu; Park, Kate G.; Lim, Tae Hyeon; Kim, Moon Suk; Choi, Hak Soo; Park, Chan Hum; Lee, Sang Jin (Bioengineering and Translational Medicine, 2021)
Cell-based tissue engineering strategies have been widely established. However, the contributions of the transplanted cells within the tissue-engineered scaffolds to the process of tissue regeneration remain poorly understood. Near-infrared (NIR) fluorescence imaging systems have great potential to non-invasively monitor the transplanted cell-based tissue constructs. In this study, labeling mesenchymal stem cells (MSCs) using a lipophilic pentamethine indocyanine (CTNF127, emission at 700 nm) as a NIR fluorophore was optimized, and the CTNF127-labeled MSCs (NIR-MSCs) were printed embedding in gelatin methacryloyl bioink. The NIR-MSCs-loaded bioink showed excellent printability. In addition, NIR-MSCs in the 3D constructs showed high cell viability and signal stability for an extended period in vitro. Finally, we were able to non-invasively monitor the NIR-MSCs in constructs after implantation in a rat calvarial bone defect model, and the transplanted cells contributed to tissue formation without specific staining. This NIR-based imaging system for non-invasive cell monitoring in vivo could play an active role in validating the cell fate in cell-based tissue engineering applications.
Keywords: Mesenchymal stem cell; Near infrared (NIR) fluorescence imaging; Near-infrared fluorescent; Tissue constructs; Tissue engineering applications; Tissue formation; Tissue-engineered scaffolds; Transplanted cells; near-infrared fluorescence; non-invasive monitoring; scaffold monitoring; stem cell tracking